Primary care physicians' perspectives on respiratory syncytial virus (RSV) disease in adults and a potential RSV vaccine for adults. Issue 4 (21st January 2019) - Hurley, Laura P.; Allison, Mandy A.; Kim, Lindsay; O'Leary, Sean T.; Crane, Lori A.; Brtnikova, Michaela; Beaty, Brenda L.; Allen, Kristen E.; Poser, Sarah; Lindley, Megan C.; Kempe, Allison
Abstract: Background: Deaths attributable to respiratory syncytial virus (RSV) among adults are estimated to exceed 11, 000 annually, and annual adult hospitalizations for influenza and RSV may be comparable. RSV vaccines for older adults are in development. We assessed the following among primary care physicians (PCPs) who treat adults: (1) perception of RSV disease burden; (2) current RSV testing practices; and (3) anticipated barriers to adoption of an RSV vaccine. Methods: We administered an Internet and mail survey from February to March 2017 to national networks of 930 PCPs. Results: The response rate was 67% (620/930). Forty-nine percent of respondents (n = 303) were excluded from analysis as they reported never or rarely caring for an adult patient with possible RSV in the past year. Among respondents who reported taking care of RSV patients (n = 317), 73% and 57% responded that in patients ≥ 50 years, influenza is generally more severe than RSV and that they rarely consider RSV as a potential pathogen, respectively. Most (61%) agreed that they do not test for RSV because there is no treatment. The most commonly reported anticipated barriers to a RSV vaccine were potential out-of-pocket expenses for patients if the vaccine is not covered by insurance (93%) and lack of reimbursement for vaccination (74%). Conclusions: Physicians reported little experience with RSV disease in adults. They are generally not testing for it and the majority believe that influenza disease is more severe. Physicians will require more information about RSV disease burden in adults and the potential need for a vaccine in their adult patients.